SYNTHESIS AND REACTIVITY OF (PHENYLSILATRANE)MANGANESE TRICARBONYL PERCHLORATE - MOLECULAR-STRUCTURE OF [(ETA-5-1-N(CH2CH2O)3SI-6-PHC6H5)MN(CO)3] - LEE, YA; CHUNG, YK; KIM, Y; JEONG, JH; CHUNG, G; LEE, D (AMER CHEMICAL SOC, 1991)
[{N(CH2CH2O)3SiC6H5}Mn(CO)3]ClO4 (1) undergoes regioselective reaction with RMgBr (R = Ph, Me, Et) in CH2Cl2 to give [eta-5-1-(N(CH2CH2O)3Si)-6-(R)C6H5]Mn(CO)3 (2a, R = Ph; 2b, R = Me; 2c, R = Et), with EtLi in THF to yield [eta-5-2-(N(CH2CH2O)3Si)-6-(R)C6H5]Mn(CO)3 (3c, R = Et), and with RMgBr (R = Ph, Me, Et), LiCH2CO2CMe3, LiCH2CN, and Li activated CHS(CH2)3S in THF to yield [eta-5-3-(N(CH2CH2O)3Si)-6-(R)C6H5]Mn(CO)3 (4a, R = Ph; 4b, R = Me; 4c, R = Et; 4e, R = CH2CO2CMe3; 4j, R = CH2CN; 4k, R = activated CHS(CH2)3S). However, 1 does not react regioselectively with the carbanions from isobutyronitrile, acetone, or tert-butyllithium or with sodium cyanide. The selectivity of the nucleophilic addition to 1 is strongly dependent on the nucleophile and reaction medium. The structure of 2a has been confirmed by X-ray diffraction: space group P1BAR; a = 9.169 (2) angstrom, b = 9.905 (2) angstrom, c = 12.353 angstrom, alpha = 110.25 (2)-degrees, beta = 97.33 (1)-degrees, gamma = 97.70 (2)-degrees; final error indices R = 0.042, R(G) = 0.043 for 2856 unique data with I > 3-sigma(I).
Keywords: CARBANION ATTACK; COMPLEXES; ARENE; AZASILATRANES; REGIOSELECTIVITY